THE EFFECTIVENESS OF LANGUAGE PROGRAM TOWARDS STUDENTS SPEAKING SKILL IN UNIVERSITY - Tarihoran, Sasmita; Jufrizal, Jufrizal (University of Kuningan, 2024)
This study examines the impact of a language program on the speaking skills of students at UIN SYAHADA Padangsidimpuan. With English proficiency being crucial for global communication, the research aimed to assess the program's effectiveness in improving students' speaking abilities. Using an ex post facto research design, 43 English department students were assessed. Speaking tests were administered at the start and end of the semester, and the data were analyzed using the Wilcoxon test. Findings showed a modest increase in mean scores, indicating some positive effect of the program. However, greater variability in post-test scores and a Wilcoxon test significance value of 0.146 suggested no statistically significant enhancement in speaking skills. This study underscores the necessity for customized interventions and enhanced teaching strategies to improve the efficacy of language programs in universities.